Spectrum of Splenectomy lesions- a 12 year study at tertiary health centre - Sweety Vijay Shinde; Sukeshni Pradeep Daiwile (Tropical Journal of Pathology and Microbiology, 2022)
Introduction: Splenectomy can be for a therapeutic, diagnostic, or incidental purpose. The spleencan be involved in a plethora of lesions. The purpose of the present study was to evaluatesplenectomy specimens for gross and microscopy.Materials & Methods: An observationalretrospective-prospective study over 12 years period. All surgically resected spleens at our tertiarycare centre were evaluated for clinical, radio-laboratory investigations, gross parenchymal andmicroscopical findings.Results: Amongst 125 splenectomies, males (73.6%) and aged 20-29(34.4%) predominated. Therapeutic indications (90.4%) included laceration, splenomegaly,hypersplenism, repeated blood transfusion, splenitis and infarction. Diagnostic indications (8.0%)had cyst, abscess and lymphoma. The mean splenic weight was 480.9 grams. The highest gross-microscopy agreement related to the capsular breach, cyst, infarct and hilar vessel thrombi, whilehilar lymph node and spleniculi showed minor disagreement.Conclusions: Meticulous grossexamination shows excellent concordance with microscopy. Diligent dissection of hilar structuresproves fruitful.